Urban and rural medium voltage networks reliability assessment - Mohd Ikhwan, Muhammad Ridzuan; Noorfatin Farhanie, Mohd Fauzi; Nur Nabihah Rusyda, Roslan; N., Md. Saad (Springer Nature, 2020)
Distribution network operators typically produce a report of network performance for all networks as a whole, by not segregating it in a different area; urban and rural networks. Although the report is sufficient, it does not represent the actual performance of each urban and rural networks. Therefore, this paper presents the configurations, parameters, and component rating for medium voltage urban and rural distribution networks. Both networks are assessed with analytical and Monte-Carlo simulation techniques. Each assessment was correlated with Energy Regulator requirements for accurate results. Urban area has better network performance due to sophisticated network automation and network configuration with n-1 or n-2 security compared to the rural area.